One-Step Alkaline-Hydrogen Peroxide Degumming of Hemp Fiber: Optimization for Enhanced Processability and Eco-Efficiency - Huanghuang Chen; Zhen Wang; Bo Jiang; Mingfang Liu; Huanghuang Chen; Bifeng Luo; Wenxiang Hong (BioResources)
Hemp fiber, as a renewable bio-based material, holds significant potential in the textile and paper industries. To unlock this potential, a critical step involves purification of the fibers. However, conventional degumming methods suffer from high energy consumption, severe fiber damage, and environmental pollution. This study evaluated a proposed one-step alkaline-hydrogen peroxide degumming process under mild conditions to achieve high-value utilization of hemp crops. Orthogonal experiments were conducted to optimize reaction conditions, including temperature, time, and liquid-to-solid ratio. Results showed that under optimal conditions (80°C, 4 h, 10:1 liquid-to-solid ratio), the residual gum content was 7.68% and fiber crystallinity increased by 8.33%. Additionally, the proportion of short fibers increased while coarse fibers decreased, yielding paper with a tensile index of 190 N/m and a whiteness of 70.3%. This low-temperature degumming process effectively removed gums while minimizing fiber damage, offering an eco-friendly and industrially viable solution for hemp fiber applications.